Um estudo dos indicadores de qualidade em escola privada confessional - Gomes, Patricia Fernandes (Universidade do Vale do Rio dos Sinos, 2014)
The aim of the research was to analyze quality indicators to education professionals of a private school in Porto Alegre, Rio Grande do Sul. It intends to place emphasis on the secondary student evaluation process. Parents, students, teachers and managers from Colégio X showed their perceptions of those forces in the evaluation process. Questionnaires to parents and students, and interviews with teachers and managers were in the methodology applied for gathering information for further qualitative and quantitative analysis. The qualitative study clarified the polissemic meaning of quality in evaluation process, observing variables like time, space and indiosyncrasy in industrial and, later, educational procedures. Indicators of qualified education from various authors and associated with the ones excerpted from the research were used in the questionnaires and interviews. As a conclusion mainly most indicators of quality were similar to cognitive and affective connection in learning environment, to technology, and to resources in learning environment. Other indicators of quality were mentioned. Teachers cited their continued development and earnings, interdisciplinary and fieldworks; while, managers mentioned the student grade control and their religious formation as an indicator of quality. The quantitative study indicated more agreements and fulfillments according to the initial forces proposed in the research, although some divergences also emerged on. To parents and students, the integration of science, ethics and moral in the evaluation process were listed; to managers, the continued development of teachers and managers were most cited.
Keywords: Qualidade; Indicadores; Educação; Avaliação; Escola privada confessional; Quality; Indicators; Education; Evaluation; Denominational School; ACCNPQ::Ciências Humanas::Educação